Differences in antiretroviral scale up in three South African provinces: the role of implementation management - Van Rensburg Dingie; Coetzee David; Schneider Helen; Gilson Lucy (BMC, 2010)
Abstract Background South Africa's antiretroviral programme is governed by defined national plans, establishing treatment targets and providing funding through ring-fenced conditional grants. However, in terms of the country's quasi-federal constitution, provincial governments bear the main responsibility for provision of health care, and have a certain amount of autonomy and therefore choice in the way their HIV/AIDS programmes are implemented. Methods The paper is a comparative case study of the early management of ART scale up in three South African provincial governments - Western Cape, Gauteng and Free State - focusing on both operational and strategic dimensions. Drawing on surveys of models of ART care and analyses of the policy process conducted in the three provinces between 2005 and 2007, as well as a considerable body of grey and indexed literature on ART scale up in South Africa, it draws links between implementation processes and variations in provincial ART coverage (low, medium and high) achieved in the three provinces. Results While they adopted similar chronic disease care approaches, the provinces differed with respect to political and managerial leadership of the programme, programme design, the balance between central standardisation and local flexibility, the effectiveness of monitoring and evaluation systems, and the nature and extent of external support and programme partnerships. Conclusions This case study points to the importance of sub-national programme processes and the influence of factors other than financing or human resource capacity, in understanding intervention scale up.